Intervention effects in NPI licensing: A quantitative assessment of the scalar implicature explanation. Issue 1 (20th April 2018) - Denić, Milica; Chemla, Emmanuel; Tieu, Lyn
Abstract : This paper reports on five experiments investigating intervention effects in negative polarity item (NPI) licensing. Such intervention effects involve the unexpected ungrammaticality of sentences that contain an intervener, such as a universal quantifier, in between the NPI and its licensor. For example, the licensing of the NPI any in the sentence * Monkey didn't give every lion any chocolate is disrupted by intervention. Interveners also happen to be items that trigger scalar implicatures in environments in which NPIs are licensed (Chierchia 2004 ; 2013 ). A natural hypothesis, initially proposed in Chierchia (2004 ), is that there is a link between the two phenomena. In this paper, we investigate whether intervention effects arise when scalar implicatures are derived.